2020
DOI: 10.1158/1055-9965.epi-20-0051
|View full text |Cite
|
Sign up to set email alerts
|

Association between Dietary Tomato Intake and the Risk of Hepatocellular Carcinoma: The Singapore Chinese Health Study

Abstract: Background: Intake of tomato and/or lycopene has been associated with reduced risk of several cancers, but there is no report on the association with risk of hepatocellular carcinoma (HCC). Methods:The associations of tomato and lycopene consumption with risk of HCC were examined in the Singapore Chinese Health Study, a prospective cohort of 63,257 Chinese aged 45-74 years at enrollment. Diet was assessed using a validated semi-quantitative food frequency questionnaire. Cox proportional hazard regression model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Intake of tomato and/or lycopene has been associated with reduced risk of several cancers, such as hepatocellular carcinoma [ 17 ], gastric cancer [ 18 ] and prostate cancer [ 19 ]. It has been proposed that lycopene, found in high amounts in tomato, may contribute to cancer prevention, which could be the biological mechanisms in the lower development of cancers with higher consumption of tomato, [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intake of tomato and/or lycopene has been associated with reduced risk of several cancers, such as hepatocellular carcinoma [ 17 ], gastric cancer [ 18 ] and prostate cancer [ 19 ]. It has been proposed that lycopene, found in high amounts in tomato, may contribute to cancer prevention, which could be the biological mechanisms in the lower development of cancers with higher consumption of tomato, [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Singapore Chinese Health Study is a prospective population-based cohort study that recruited 63,257 Chinese men and women, aged 45–74 years, in Singapore, between April 1993 and December 1998 [ 31 ]. The eligible subjects had to be permanent residents of Singapore government-built housing and belong to one of two major Chinese dialect groups—Hokkien or Cantonese.…”
Section: Methodsmentioning
confidence: 99%
“…Lycopene, a bioactive deep-red pigment naturally synthesized by fruits and vegetables, is the most abundant carotenoid in red tomatoes and tomato-based products, including ketchup, tomato juice, and pizza sauce ( Ilahy et al, 2019 ). Human and experimental studies have reported that lycopene can influence the development and progression of HCC ( Mein et al, 2008 ; Ip and Wang, 2013 ; Stice et al, 2018 ; Thomas et al, 2020 ). For instance, in studies conducted using hepatoma cell lines lycopene inhibited cell growth, migration, and invasion ( Huang et al, 2008 ; Yang et al, 2012 ; Jhou et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%